Patent Reform - Polanvyi, Michael (Review of Economic Studies, 1944)
Journal Article Patent Reform Get access Michael Polanvyi Michael Polanvyi Manchester Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 11, Issue 2, 1944, Pages 61–76, https://doi.org/10.2307/2295967 Published: 01 January 1944